ANALISIS FRAUD HEXAGON MODEL TERHADAP KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN SUB SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Apsari, Hirawresti Langen; Gondo, Imelda (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to analyze of the fraud hexagon model, namely pressure which is proxied by financial targets and financial stability, capabilities that are proxied by changes in directors, opportunities proxied by ineffective monitoring, rationalization proxied by change in auditors, arrogance proxied by frequent number of CEO's picture, and collusion proxied by government projects, political connections and state-owned enterprises to financial statement fraud. The sample of this study is property and real estate sub sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2022. This study uses secondary data, namely financial reports and annual reports. The samples of this study consist of 85 companies with 340 unit analysis with purposive sampling technique. This study uses the data panel regression analysis technique with EViews 12 analysis tool. The results of this study found that the elements of pressure, capability and rationalization measured through financial targets, change of directors and change in auditors had a significant effect on financial statement fraud. Meanwhile, financial stability, ineffective monitoring, frequent number of CEO's pictures, government projects, political connections and state-owned enterprises have no significant effect on financial statement fraud in property and real estate sub sector companies listed on the IDX in 2019-2022.